Report of the Working Group on Minor Irrigation for Formulation of the Tenth Plan (2002-2007) Proposals - Planning Commission (Planning Commission, 2001)
The Working Group on Minor Irrigation Programme for formulation of the tenth five year plan (2002-2007) was constituted by the Planning Commission vide their letter No.25(l) D-2000-WR, Nov, 20th 2000, Dec. 19th, 2000 and March 2nd, 2001 (Appendices 1,2,3) Shri M.S. Billore, Former Secretary, Water Resources Deptt., Madhya Pradesh was appointed as Chairman of the Working Group.
Government of India
Ministry of Water Resources Minor Irrigation Division